2020
DOI: 10.1097/md.0000000000021548
|View full text |Cite
|
Sign up to set email alerts
|

Improving staff safety with checklists during novel coronavirus disease (COVID-19) pandemic

Abstract: Novel coronavirus disease (COVID-19) emerged in Wuhan in December 2019, has spread in many countries affected people globally. In response to the economic requirement of the nation and meet the need of patient's, a momentous event was going back to work step by step as fighting against COVID-19. Safety in clinical work is of priority as elective surgery in the department of surgery progressing. We used checklists based on our experiences on COVID-19 control and reality of clinical work from February to March i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…This recommendation is also aligned with a study performed in China during the early COVID-19 pandemic. Jing et al used checklists for the staff in a vascular surgical department to screen patients, verify the cleanliness and safety of the environment, and monitor their own health conditions and compliance with infection control 19 . The Centers for Disease Control and Prevention (CDC) also released several preparedness checklists during the early pandemic for healthcare professionals and organizations to adopt in evaluating and managing COVID-19 patients, infection control, and contact tracing 20-22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This recommendation is also aligned with a study performed in China during the early COVID-19 pandemic. Jing et al used checklists for the staff in a vascular surgical department to screen patients, verify the cleanliness and safety of the environment, and monitor their own health conditions and compliance with infection control 19 . The Centers for Disease Control and Prevention (CDC) also released several preparedness checklists during the early pandemic for healthcare professionals and organizations to adopt in evaluating and managing COVID-19 patients, infection control, and contact tracing 20-22 .…”
Section: Discussionmentioning
confidence: 99%
“…Jing et al used checklists for the staff in a vascular surgical department to screen patients, verify the cleanliness and safety of the environment, and monitor their own health conditions and compliance with infection control. 19 The Centers for Disease Control and Prevention (CDC) also released several preparedness checklists during the early pandemic for healthcare professionals and organizations to adopt in evaluating and managing COVID-19 patients, infection control, and contact tracing. [20][21][22] Although there are no current data to show the efficacy and impact of using the checklists created by the CDC, checklists may provide a standardized comprehensive step-by-step guide for healthcare organizations to manage patients with the most updated evidence, develop a contingency plan, and monitor for its effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Verification of tools and individuals (patients) 4. Verification of mentoring and education From the results of the research using the safety checklist on 840 respondents, it was found that the overall adherence increased from week 1 (72.4%) to week 4 (91.0%) (P <0.01 based on the chi-square test (Huang, Liu, Wu, Zhang, & Yang, 2020) Patient Safety-Based Nursing Care Service System Patient safety is a basic principle in health care. Patient safety at the hospital is a system in which the hospital makes patient care safer.…”
Section: Nursing Care Managementmentioning
confidence: 99%
“…To increase patient safety during a pandemic, proper clinical governance is needed in providing nursing care, one of the governance that can be done is by using a summarized checklist system (Huang et al, 2020) The check list can prevent and minimize medical errors because this method ensures the important steps in a sequential treatment process according to the right steps, so as to improve compliance behavior and preventive measures to increase personal protection to minimize risks. Research conducted from 2009 to 2016 shows the effectiveness of standardization, application and sustainability of the use of the checklist .…”
Section: Nursing Care Managementmentioning
confidence: 99%